FACTOR AFFECTING DIVIDEND POLICY IN FINANCIAL SECTOR COMPANIES IN INDONESIA STOCK EXCHANGE - Magdalena, Katherine; Santioso, Linda (International Journal of Application on Economics and Business, 2023)
This study aims to analyze the effect of profitability, liquidity, leverage, firm size and free cash flow on dividend policy in financial sector company listed on the ISE in the 2018-2020 period. This research’s sample used 25 companies listed on the Indonesia Stock Exchange. The hypothesis in this study used multiple regression analysis. The data processing in this study uses the E-views application version 12. The results of this study indicate that the variables of profitability and firm size have a significant effect and positive on dividend policy, the variables of liquidity have a significant effect and negative on dividend policy, while the variables of leverage and free cash flow do not have a significant effect on dividend policy.